(untitled) (Experimental biology, 2017)
Changes were detected in the blood of rats caused by heavy metal compounds. The results show that the salts of heavy metals poisoning demonstrates in damage in the blood cells in the animal body and makeing weaker their immunity. As a result, various changes occur in animals. In addition, it was collected material on immunodepresiv exposure to heavy metals in the body of rats MPC 25, 50, 75, 100 times more compounds of zinc ions, lead and cadmium. Animals’ disorders were observed in the nervous system, including tearing, inflammation conjunctival sac and certain groups even with bleeding. Leukogram, which was made by the blood of rats, showed that the poisoning caused by the impact of three types of heavy salts, has led to significant changes in the health and behavior of the animals. During uvelechenie number of MAC 100 times more salt poisoning three compounds in animal organisms have been found strong signs of poisoning,finally, all experimental rats died within 5-6 days. It is important to note, animals poisoned by 75-100 times the maximum permissible concentration of heavy metal salts of the three have died. At 100-fold increased number of MPC led to fatal death, especially by the poisoning of three compounds salts. Leukogram blood of experimental rats showed that, in the blood of rats, poisoned by three salts, during neutrophilia and lymphopenia, leukopenia was found. Neutrophils are characteristic granulated toxicity and gipersigmatich core.